Design of flapping mechanism and analysis on the lift force of the wings / Saktishvikmend Anbalagan - Saktishvikmend, Anbalagan (2019)
Development of flapping unmanned air vehicle (FUAV) has been of interest in the aerospace community with ongoing research. Most of the previous research were done on pitching and plunging motion of the FUAV. With pitching and flapping motion of FUAV, researchers usually study it by experiment such as wing tunnel. A few works were reported by numerical calculation. In this paper, a flapping wing mechanism was developed and the capabilities of flapping was analyzed. A mechanical based mechanism is designed for the flapping motion. Three different shapes of wings were used in this project. Preliminary analysis has been done on the wings. Numerical analysis and structural analyses has been done on the mechanisms. The model was designed in Solid Works. The mechanism uses gear and metal rods, shaft, spars, and a DC motor to drive the gear. The complete wing span used in the project is about 110 mm. Analyses were done based on Solid Works simulation analysis. This research is helpful to understand the flight mechanism of birds, thus improving the design of FUAV simulating birds.